PHYSIOLOGICAL RESPONSE OF SEEDS OF PEANUT GENOTYPES TO WATER DEFICIENCY - Carrega, Willians Cesar [UNESP]; Rocha Barbosa Martins, Pedro de Figueiredo [UNESP]; Bacha, Allan Lopes [UNESP]; Cesarin, Anne Elise [UNESP]; Oliveira, Thiago Souza [UNESP]; Godoy, Ignacio Jose de; Costa Aguiar Alves, Pedro Luis da [UNESP] (Univ Federal Uberlandia, 2019)
Among the factors that may influence the germination process of seeds, water deficiency is considered the most important. The present study aims to evaluate the physiological response of peanut genotypes to water deficiency. The experiment was conducted in a completely randomized design with four replications in a 12 x 7 factorial scheme with 12 peanut genotypes and seven polyethylene glycol 6000 concentrations corresponding to osmotic potentials of 0.00; -0.10; -0.20; -0.40; -0.60; -0.80 and -1.00 MPa. The data were submitted to analysis of variance and Tukey's test at a 5% probability level and, when significant, to analysis of variance adjusted to a quadratic polynomial curve. The germination percentage, seed vigor evaluated by the speed germination index, mean germination time, root length and root dry matter of some genotypes were affected by the osmotic potentials. Among the genotypes, there is a differential response related to the water deficiency level. In relation to the physiological response of the seeds, the lineages 506, 599, and 870 and the cultivar IAC Tatu-ST have a higher tolerance of water deficit. The peanut genotypes begin to suffer the effects of water deficiency at the osmotic potential of -0.4 MPa.
Keywords: Arachis hypogaea L; PEG 6000; Osmotic potential; Water restriction; Germination